Agricultural Risk and the Spread of Religious Communities - Philipp Ager; Antonio Ciccone (European Historical Economics Society (EHES), 2015)
Building on the idea that members of religious communities insure each other against some idiosyncratic risks, we argue that religious communities should be more widespread where populations face greater common risk. Our empirical analysis exploits rainfall risk as a source of common agricultural risk in the nineteenth-century United States. We show that a greater share of the population was organized into religious communities in counties with greater rainfall risk. The link between rainfall risk and membership in religious communities is stronger among more agricultural counties and counties exposed to greater rainfall risk during the growing season.
Keywords: Z12; O13; N31; 330; Religious community membership; agricultural risk; informal insurance